Sports marketing's characteristics - Fallatah, Badr; Altowerqi, Zayed (Journal of Physical Education, 2023)
Sports marketing has established itself over the last three decades not only as a very special form of marketing, but also as a subject of research. However, it is quite surprising that the nature of sports marketing is relatively unknown, as different definitions of sports marketing seem to indicate. In fact, there is currently no universally agreed-upon definition of sports marketing, and views on the subject are quite divergent. This paper examines the nature of sports marketing and therefore seeks to contribute to the ongoing discussion as to whether sports marketing is any different from principal marketing or just a modified version Three distinct definitions of sports marketing are discussed at the outset. Then the unique characteristics of sports and sports marketing are described followed by the implications for sporting organizations, companies involved in sports marketing, and sports marketing academics. The paper concludes with a summary of the concept of sports marketing that illustrates the very special nature of sports marketing both verbally and graphically.     The mission of sport marketers is to raise brand awareness of the products and services available to consumers, regardless of the nature and level of sports, which are all necessary to boost events’ attendance and generate excitement. For a successful marketing, sport marketers must first conduct a thorough consumer research analysis to learn about the target audience’s needs, motivations and interests pertaining to the promoted product or service. When a business is enthusiastic about satisfying its clients and seeks to establish enduring connections that benefit the business and its stakeholders, that is a sign of an effective marketing strategy. (Kotler & Keller, 2011). Traditionally, the marketing mix consists of the following four elements: product, price, place, and promotion.